Perceptions of educational managers about the effectiveness of selected training programmes: a case study in the Ministry of Education, Oman - Salim Juma Alaraimi, Aisha; Othman, Azam (IIUM Press, 2015)
The present study evaluated the characteristics and effectiveness of selected training programmes for educational manager in the MoE in the Sultanate of Oman. The study investigated the effectiveness of training programmes for educational managers. Nine (9) participants were specifically selected for interview using the snowball sampling technique. The findings showed that human resource development (HRD) is undertaking intensive efforts in distributing training culture among MoE staff, 78% of the interviewers were not satisfied with training approaches and methods adopted by the trainers. Furthermore, the findings revealed that trainees were satisfied with the suitability and adequateness of training techniques, training aids and training resources. Among the findings study contributed to the body of knowledge by generating frameworks useful for measuring the characteristics and effectiveness of training programme and competence levels of educational managers. It is recommended that the MoE should ensure upgrading and extending of the existing training infrastructure at the ministry and also consider prospective trainers to a training programme. This study is likely to be of interest to those stakeholders dealing with training in education, not only in the MoE but in other institutions where training of managers are vital.